Oleic acid promotes prostate cancer malignant phenotype via the G protein‐coupled receptor FFA1/GPR40. Issue 9 (16th April 2018) - Liotti, Antonietta; Cosimato, Vincenzo; Mirra, Paola; Calì, Gaetano; Conza, Domenico; Secondo, Agnese; Luongo, Gelsomina; Terracciano, Daniela; Formisano, Pietro; Beguinot, Francesco; Insabato, Luigi; Ulianich, Luca
Abstract : Prostate cancer (PCa) is the most commonly diagnosed malignancy in men and the second leading cause of cancer‐related death in industrialized countries. Epidemiologic evidence suggests that obesity promotes aggressive PCa. Recently, a family of Free Fatty Acid (FFA) receptors (FFARs) has been identified and reported to affect several crucial biological functions of tumor cells such as proliferation, invasiveness, and apoptosis. Here we report that oleic acid (OA), one of the most prevalent FFA in human plasma, increases proliferation of highly malignant PC3 and DU‐145 PCa cells. Furthermore, docetaxel cytotoxic action, the first‐line chemotherapeutic agent for the treatment of androgen‐independent PCa, was significantly reduced in the presence of OA, when measured by the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide assay, suggesting that this FFA plays also a role in chemoresistance. OA induced intracellular calcium increase, in part due to the store operated calcium entry (SOCE), measured by a calcium imaging technique. Moreover, PI3K/Akt signaling pathway was enhanced, as revealed by increased Akt phosphorylation levels. Intriguingly, attenuating the expression of FFA1/GPR40, a receptor for long chain FFA including OA, prevented the OA‐induced effects. Of relevance, we found that FFA1/GPR40 is significantly overexpressed in tissue specimens of PCa, compared to benign prostatic hyperplasia tissues, at both mRNA and protein expression level, analyzed by Real Time RT‐PCR and immunofluorescence experiments, respectively. Our data suggest that OA promotes an aggressive phenotype in PCa cells via FFA1/GPR40, calcium and PI3K/Akt signaling. Thus, FFA1/GPR40, might represent a potential useful prognostic biomarker and therapeutic target for the treatment of advanced PCa. Abstract : Oleic acid induces proliferation and resistance to docetaxel in prostate cancer cells via FFA1/GPR40 ‐ FFA1/GPR40 is overexpressed in prostate cancer tissues.